PROSPEK IMPLEMENTASI KONVENSI PERUBAHAN IKLIM DALAM PENGELOLAAN HUTAN INDONESIA - Yayuk Siswiyanti; Dudung Darusman; Hariadi Kartodihardjo; Iin Ichwandi (Jurnal Analisis Kebijakan Kehutanan, 2015)
The earth atmosphere temperature is rising due to the increasing greenhouse gases. Facing the problem, the international community establishes the Climate Change Convention. One of main activities mention in that convention is to reduce deforestation and forest degradation. It has been four decades Indonesia ratified various convention relating to forest sustainability but the deforestation and forest degradation is still accelerating. This study analyzes the compatibility of the conventions on climate change in forest management in Indonesia. The research uses the narrative analysis method. Main result of the research shows that there is a discrepancy between the narrative of convention on climate change and the management of Indonesia forest. The work of the convention in Indonesia forest management requires some options related to incentives and fair access to forest uses.